Telephone follow-up of oncology patients: the contribution of the nurse specialist for a Service-Dominant Logic in hospital - Corinne Rochette; Anne Sophie Michallet; Stéphanie Malartre-Sapienza; Sophie Rodier (BMC, 2021)
Abstract Background The French healthcare system is characterised by a shift towards outpatient care and the desire to develop telemedicine affirmed in the collective commitment "Ma santé 2022" presented by President Macron in 2018. In France, remote patient follow up has recently been developed in the active phase of cancer treatment inspired by the patient navigation approach used in other countries. According to Service-Dominant Logic (S-D L), patients become more active. Their role in co-production of services is strengthened and their behaviours changed. Telephone follow-ups can contribute to modifying the relationship between the patient and the nurse navigators in charge of it, moving logically from a passive attitude from the patient to a more active one. Methods This study was carried out at Léon Bérard, a cancer control unit, in France. It concerned patients treated in an oncohaematology department, who benefited from telephone follow-ups carried out by nurse specialists during the active phase of their treatment. The multidisciplinary research team including social science researchers, physicians and carers developed a research protocol to study this pilot case. Essentially based on a qualitative approach, it was validated by the centre's management to study this follow-up on patients' behaviours. The 1st phase of the research, based on 24 semi-structured interviews with patients undergoing treatment undertaken from November 2018 to September 2019, is presented. Results The Telephone follow-up was a positive experience for all patients. The action of the nurse specialist helped to develop certain dimensions of in-role and extra-role behaviour that created value. The patients' discourse has reported a positive follow-up in its clinical dimensions, its psychological dimensions and an enhanced quality of life. We detected a patient activation through their roles but it remained limited. The telephone follow-up also created a patient dependency. Conclusions The telephone follow-up is a relevant tool for patients undergoing treatment and it deserves to be more widely deployed. It brings comfort and creates a relationship based on trust but at the same time it limits the emancipation of the patient, which is a central element of the S-D logic and its empowerment.